Hubungan Regulasi Emosi dengan Gejala Depresi pada Remaja SMA yang Memiliki Orang Tua Bercerai - Rania, Cut Fahira Putri; Roswiyani (Jurnal Syntax Admiration, 2024)
The aim of this study was to understand the relationship between adolescents' emotional regulation abilities and the level of depressive symptoms they experienced after their parents divorced. This research uses a non-probability sampling technique by drawing the number of samples using a purposive sampling technique with the criteria being teenagers in grades 10 to 12 of high school, aged between 15 and 18 years, residing in one of the regions of West Java. This research uses a correlational quantitative research strategy. The data collection method is carried out through offline questionnaires. . The results of analysis using Pearson correlation showed that there was a negative relationship between emotional regulation and depressive symptoms in adolescents after their parents' divorce (r = -0.634, p = .000 < 0.05). This shows that if emotional regulation is low then depressive symptoms will be high, and vice versa. The benefit of this research is that it provides a deeper understanding of the importance of emotional regulation in dealing with stress and difficult situations, especially for teenagers who experience their parents' divorce. .